STUDY ON LARVAL DENSITY OF AEDES MOSQUITOES IN NCR DURING DURING PRE AND POST MONSOON SEASON - Basra, Gurpreet Kaur; Singh, Sukhvir; Upadhyay, Preeti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Aedes mosquito is a vector for transmitting many arboviruses. Since last few years, annually more than one lakh cases of dengue infections occur in India resulting in substantial rates of mortality and morbidity. Thus, the aim of this study was to determine the presence of Aedes larva during different seasons in areas where Dengue cases were high and to highlight the importance of vector control at regular intervals to ensure sustained control of mosquito breeding. Study was carried for two years i.e. June and September 2018 & June and October 2019 in areas of Noida and Ghaziabad. In pre monsoon season out of 245 houses 12 were positive for Aedes breeding and in post monsoon season out of 262 houses 36 were positive in Ghaziabad. In Noida out of 190 houses 17 were positive for Aedes breeding and in post monsoon season out of 185 houses 29 were positive All the indices were found above critical level during post monsoon season in both Noida and Ghaziabad during both years, which gives an early warning signal for preventing further transmission of the disease and also to prevent further outbreak situations by taking appropriate control measures on time.